Selection of Maltodextrin and Cornstarch Suppliers Using Procurement Supplie Management and Multi-Objective Optimization on The Basis of Ratio Analysis (Moora) Methods at Pt Sari Alam Sukabumi - Domianus Paskalius; Yani Iriani (Publikasi Indonesia, 2025)
PT Sari Alam Sukabumi is a natural ingredient processing company that produces herbal extracts in the form of dry powder. In its production process, the company uses the main fillers, namely maltodextrin and cornstarch. However, during 2024 the company faces significant constraints related to raw material suppliers, such as delivery delays of up to 25% of the total schedule, high price fluctuations, and inconsistent material quality. The symptoms of these problems have an impact on the inhibition of the production process, increased operational costs, and disruptions in the distribution schedule. This research aims to assist companies in determining the most optimal supplier of maltodextrin and cornstarch raw materials based on various evaluation criteria, namely price, quality, service, timeliness of delivery, and accuracy of delivery quantity. The specific objective of this study is to identify important criteria in supplier selection using the Procurement Supplier Management (PSM) approach and apply the Multi-Objective Optimization on the Basis of Ratio Analysis (MOORA) method to obtain the best ranking of available supplier alternatives. This type of research is descriptive with a quantitative approach. Data was collected through interviews, questionnaires to five internal company respondents, and documentation. The research process included determining five main criteria—price, quality, service, timeliness, and accuracy of delivery quantity—which were then weighted based on respondents' assessments. Furthermore, supplier performance data is processed using the MOORA method to obtain ranking results.